The alleged mummies of the Pandone family in the conventual church of San Francesco at Prata Sannita, Caserta (southern Italy) - Ventura, Luca; Salzillo, Cecilia; Forte, Veronica; Valente, Franco (Medicina Historica, 2025)
Monastic and conventual communities in central and southern Italy have historically preserved human remains, either intentionally or through spontaneous mummification facilitated by the region’s cold, dry climate. Here we present a preliminary investigation of a previously undocumented collection of three mummies housed in the conventual church of San Francesco in Prata Sannita, Caserta. These remains have traditionally been attributed to Scipione Pandone, his wife, and their daughter, though definitive identification remains uncertain due to the absence of textual evidence. An alternative hypothesis suggests that the remains might belong to Federico Pandone (son of Scipione’s brother), his second wife, and their daughter. The mummies, previously housed in a chapel and now stored in a wall cupboard, are well-preserved on their external surfaces and show partial bandaging, suggesting the possibility of intentional preservation. The environmental conditions of the crypt may have also contributed to their spontaneous mummification. To ensure comprehensive bioanthropological and paleopathological analyses, the bodies will undergo external inspection, computed tomography (CT) scans, and minimally invasive tissue sampling for histopathological, paleonutritional, and paleogenomic studies. Additionally, textile fragments and any surviving grave goods will also be examined using advanced analytical techniques such as SEM-EDS and FT-IR spectroscopy. Aim of the study is to elucidate the health, diet, and lifestyle of the subjects. The findings will contribute to a better understanding of cultural and social practices surrounding death and burial in the Italian Apennine regions, and the results are expected to provide a scientific basis for the permanent on-site exhibition of the mummies.